(untitled) (Vietnam Journal of Community Medicine, 2024)
Aim: (1) Determine the treatment compliance rate of type 2 diabetes patients being managed at health stations in Chau Thanh A district, Hau Giang province in 2022. (2) Find out some factors related to treatment compliance of type 2 diabetes patients at health stations in Chau Thanh A district, Hau Giang province 2022. Methods: Cross-sectional on 314 outpatients over 40 years old diagnosed with Type 2 Diabetes according to ADA 2020 being managed at health stations of Chau Thanh A district, Hau province Giang in 2022 Results: The treatment compliance rate of patients according to the Morisky - 8 scale was 77%. There is a relationship between age, education level and disease duration with treatment compliance rates in patients. Specifically, patients over 60 years old have an odds ratio of 2.06 times higher for adherence to treatment than the group under 60 years old, the group with an education level above high school has an OR of adherence to treatment 2.24 times higher, and The group with disease duration over 5 years had an OR of compliance 1.775 times higher (P<0.05). Conclusion: There are still some diabetic patients who have difficulty adhering to treatment. There is a need to increase awareness and effective treatment monitoring plans for outpatients.